Solvothermal synthesis of green fluorescent carbon dots from palm kernel shells - Gayathry, Ganesh; Misnon, Izan Izwan; Rajan, Jose (Elsevier Ltd, 2023)
Carbon dots (CDs) enriched with functionalities are of great interest in biological and electrochemical applications. Herein, CDs of an average diameter of 2.5 nm were synthesized from palm kernel shells (PKS) using the solvothermal method with N-N dimethylformamide as the solvent. These CDs were shown to have fluorescence emission at 520 nm due to the presence of rich functional groups decorating the surfaces of the CDs. The developed CDs exhibited excellent photo, thermal and ionic stability. Further, these CDs were utilized as fluorescent ink, which was invisible in daylight and exhibited bright green fluorescence under UV irradiation of 365 nm. The use of DMF as the solvent in this study opens up the possibilities for the developed CDs to be used in wide applications such as optoelectronics, charge storage systems and electrospinning, without any further protocols.